2017
DOI: 10.1186/s13023-017-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype prediction for mucopolysaccharidosis type I by in silico analysis

Abstract: BackgroundMucopolysaccharidosis type I (MPS I) is an autosomal recessive disease due to deficiency of α-L-iduronidase (IDUA), a lysosomal enzyme that degrades glycosaminoglycans (GAG) heparan and dermatan sulfate. To achieve optimal clinical outcomes, early and proper treatment is essential, which requires early diagnosis and phenotype severity prediction.ResultsTo establish a genotype/phenotype correlation of MPS I disease, a combination of bioinformatics tools including SIFT, PolyPhen, I-Mutant, PROVEAN, PAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Even though the crystal structure of IDUA complexed with various substrates has been published, the conformation of the active site defined, and it has been shown that the high mannose glycan at Asn372 contributes to the enzymatic activity, it still remains a challenge to use this structure directly to a priori predict the functional effect of sequence variants on the processing and enzymatic activity of the protein . Most of the recurrent variants reported here have been discussed in relation to in silico structural and functional effects on the IDUA protein and although one can use these various models to explore the effects of variants on protein structure, the real‐life data reported through the Registry is invaluable and arguably more relevant to clinical management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the crystal structure of IDUA complexed with various substrates has been published, the conformation of the active site defined, and it has been shown that the high mannose glycan at Asn372 contributes to the enzymatic activity, it still remains a challenge to use this structure directly to a priori predict the functional effect of sequence variants on the processing and enzymatic activity of the protein . Most of the recurrent variants reported here have been discussed in relation to in silico structural and functional effects on the IDUA protein and although one can use these various models to explore the effects of variants on protein structure, the real‐life data reported through the Registry is invaluable and arguably more relevant to clinical management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…SAAMP 2.0 yielded a total sensitivity of 94.9% (95.1% in IDS , 95.1% in IDUA and 94.3% in GLB1 ), and a specificity of 89.7%. Considering the importance of early diagnosis, even a seemingly small increase in sensitivity and specificity represents a significant improvement over the SAAMP 1.0 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 bioinformatics tools were used as previously described . These tools include SIFT (http://sift.jcvi.org/), PolyPhen (http://genetics.bwh.harvard.edu/pph2), I‐Mutant (http://gpcr2.biocomp.unibo.it/cgi/predictors/I-Mutant3.0/I-Mutant3.0.cgi), PROVEAN (http://provean.jcvi.org/index.php), PANTHER (http://www.pantherdb.org/), SNPs&GO (http://snps.biofold.org/snps-and-go/snps-and-go.html), PHD‐SNP (http://snps.biofold.org/phd-snp/phd-snp.html).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations